Polypoidal choroidal vasculopathy - Opala, Aleksandra; Terelak-Borys, Barbara; Grabska-Liberek, Iwona (Klinika Oczna / Acta Ophthalmologica Polonica, 2019)
Polypoidal choroidal vasculopathy is characterized by the presence of branching vascular network with terminal aneurysmal dilations. The disease is diagnosed based on the characteristic appearance of choroidal vessels in indocyanine green angiography. Clinically, polypoidal choroidal vasculopathy presents as orange-reddish nodular structures below the retinal pigment epithelium, associated with numerous recurrent sero-hemorrhagic retinal pigment epithelial or neuroretinal detachments, secondary to leakage and bleeding from baggy choriocapillary dilations. The lesions are located at the posterior pole, in the macular or disc area. There is no consensus on optimum treatment of polypoidal choroidal vasculopathy. Due to its changing and recurrent nature as well as the risk of permanent vision loss, bespoke therapy and long-term care are essential. Published literature discusses various treatment modifications in symptomatic polypoidal choroidal vasculopathy, including thermal laser photocoagulation, indocyanine green angiography – guided verteporfin photodynamic therapy, anti-vascular endothelial growth factor agents and combined therapy involving photodynamic therapy with anti-vascular endothelial growth factor agents.